INVENTORY PRICING AND CHANGES IN PRICE LEVELS. - McMullen, Stewart Y.; Dixon, Robert L.; Hill, Thomas M.; Lanterman, Joseph B.; Mautz, R.K.; Moonitz, Maurice; Stans, Maurice H. (The Accounting Review, 1954)
Abstract This article comments on inventory pricing and changes in price levels. Ideally, the measurement of accounting profit involves the matching precisely of the identified costs of specific units of product with the sales revenues derived there from. Secondly, where conditions are such that precise matching of identified costs with revenues is impracticable, identified cost matching may be simulated by the adoption of an assumed flow of costs. Also, a flow assumption can be realistic, in that it reflects the dominant characteristics of the actual flow of goods; thus it may reflect an actual dominance of first-in, first-out, average, or last-in, first-out movement. A flow assumption can be artificial, on the other hand, in that it premises a flow of costs that is clearly in contrast with actual physical movement. However, the periodic income of a business enterprise is computed by deducting from the revenues of the period the costs which are properly associated with those revenues. In the case of certain costs, for example sales commissions, the relationship to the revenues of a period is quite direct and the matching process is accomplished with a minimum of uncertainty.